2022
DOI: 10.1177/13684302221095757
|View full text |Cite
|
Sign up to set email alerts
|

Organizational metadehumanization and mechanistic self-dehumanization: The role of surface acting

Abstract: This research examines the relationship between metadehumanization, that is, perceiving dehumanizing treatments, and self-dehumanization, that is, perceiving oneself as less than human. We argue that, in work settings, this relationship can be explained through a behavioral mechanism. Specifically, organizational metadehumanization would drive employees to engage in more emotional labor (i.e., surface acting), which, in turn, would generate mechanistic self-dehumanizing perceptions. Our hypothesized mediation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In line with prior experimental studies on ODH (Nguyen et al, in press), we used a scenario vignette procedure to manipulate ODH (Table S1). We invited respondents to participate in a short study on the ‘employee–organization relationships in organizational settings’, which implies for them to read a short text (i.e., a hypothetical scenario) and to put themselves into the role of the supermarket cashier described in the text.…”
Section: Methodsmentioning
confidence: 99%
“…In line with prior experimental studies on ODH (Nguyen et al, in press), we used a scenario vignette procedure to manipulate ODH (Table S1). We invited respondents to participate in a short study on the ‘employee–organization relationships in organizational settings’, which implies for them to read a short text (i.e., a hypothetical scenario) and to put themselves into the role of the supermarket cashier described in the text.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Song et al (2022) revealed that conferring individuals with numerical identifications (i.e., a form of dehumanization), would trigger a higher level of self-dehumanization among them. Recently, other researchers detected that organizational dehumanization in a particular organization would motivate its staff to engage in more surface actions, and then make them carry a higher level of mechanistic self-dehumanization ( Nguyen et al, 2022 ). With that being said, while being objectified, individuals would internalize the dehumanization component of their objectification experience, which causes them to regard themselves as less human.…”
Section: Introductionmentioning
confidence: 99%